2021
DOI: 10.2147/nsa.s333467
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Application of Nanoparticles Green Synthesized Using Medicinal Plant Extracts as Novel Nanomedicines

Abstract: The use of medicinal plants in green synthesis of metal nanoparticles is increasing day by day. A simple search for the keywords “green synthesis” and “nanoparticles” yields more than 33,000 articles in Scopus. As of August 10, 2021, more than 4000 articles have been published in 2021 alone. Besides demonstrating the ease and environmental-friendly route of synthesizing nanomaterials, many studies report the superior pharmacological properties of green synthesized nanoparticles compared to those synthesized by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 167 publications
0
16
0
Order By: Relevance
“…This indicates stable grain of size according to literatures. 25,26 The result of the XRD showed the atomic arrangement, crystalline structure, crystallite size silver NPs from PC and imperfections of silver NPs. The XRD peaks (Figure 4), confirmed the presence of four significant peak between 30-70 o .…”
Section: Sem Analysismentioning
confidence: 99%
“…This indicates stable grain of size according to literatures. 25,26 The result of the XRD showed the atomic arrangement, crystalline structure, crystallite size silver NPs from PC and imperfections of silver NPs. The XRD peaks (Figure 4), confirmed the presence of four significant peak between 30-70 o .…”
Section: Sem Analysismentioning
confidence: 99%
“…The various article demonstrated that synthesized ZnONPs form the green routes extracts obtained from diverse plants which produce NPs of different sizes and shapes. ZnONPs have different shapes like nanoflowers, nanosphere, hollow sphere, hexagonal wurtzite, and nanorods were described by Pachaiappan et al, [12][13][14] . While ZnO is hydrophilic, hydrophobic films are effective in preventing biofilm adherence.…”
Section: Introductionmentioning
confidence: 97%
“…This issue can be overcome by employing biological agents, such as bacteria, fungi, algae, actinomycetes, and plants for the synthesis of metal nanoparticles (John et al 2021 ; Koul et al 2021 ; Chugh et al 2021 ; Rai et al 2021 ; Dikshit et al 2021 ). Recently, the use of plant extracts for nanoparticle synthesis has received much attention due to the rich diversity of phytochemicals, availability in bulk quantities, and simplicity (Balciunaitiene et al 2021 ; Amjad et al 2021 ; Gaddam et al 2021 ; Aboyewa et al 2021 ; Selvakesavan and Franklin 2021 ; Sawalha et al 2021 ; Rajagopal et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%